3D imaging for bite mark analysis. (1st May 2013) - Evans, S T; Jones, C; Plassmann, P
<x xml:space="preserve">Abstract</x> This work describes the investigation into a new 3D capture method for acquisition and subsequent forensic analysis of bite mark injuries on human skin. When documenting bite marks with standard 2D cameras, errors in photographic technique can occur if best practice is not followed. Subsequent forensic analysis of the mark is problematic when a 3D structure is recorded in a 2D space. A 3D image capture and processing system might avoid the problems resulting from the 2D reduction process, simplifying the guidelines and reducing errors. This paper reviews current 2D and three 3D capture methods and proposes a series of benchmarks for system assessment. This is followed by a series of performance evaluations of the existing current 2D and two 3D methods. Further proposed solutions include the design of a system specification for the practical reproducible acquisition of bite mark injuries and a review of the validation process for forensic evidence presented to the courts. The result of this work is that a 3D system is required to produce the correct 3D data of a bite mark and suspect dentition for forensic analysis. Such a system should be practical and consistent if it is to replace the current de facto 2D systems. The MAVIS hardware, for example, can be considered a practical and consistent solution for producing the required 3D image of a bite mark for analysis; however, the MAVIS hardware cannot produce a satisfactory 3D image of a dental cast. At present, a laser scanner is required to produce satisfactory results of a dental cast. Angular distortion and errors created by the user in 2D image capture can hinder the digital measurement process. 3D capture therefore introduces less operator error in the form of angular distortion.